Mainstreaming disaster risk management in higher education (2016)
Universities should actively participate in disseminating and fostering a culture for disaster risk management (DRM) among students and the community. Particularly in countries with high levels of risk, education plays a key role in raising awareness on the importance of preventing and implementing conscious risk management. Though the incorporation of DRM into the curricula, education programs become a mechanism to prepare students from a perspective of strengthening of values, citizenship, and social sensibility towards how disaster represents a disruption of the functioning of a community and impairs business activity. This paper presents the proposal for the integration of DRM of a private university in Mexico, one of the countries particularly susceptible to extreme hydrometereological and geological events. The proposal includes a concentration area for undergraduate business students, a mandatory introductory course for all business majors, and for the business community an executive education program for SMEs